Nest Etiquette—Where Ants Go When Nature Calls - Czaczkes, Tomer J. (PLoS One, 2015)
Sanitary behaviour is an important, but seldom studied, aspect of social living. Social insects have developed several strategies for dealing with waste and faecal matter, including dumping waste outside the nest and forming specialised waste-storage chambers. In some cases waste material and faeces are put to use, either as a construction material or as a long-lasting signal, suggesting that faeces and waste may not always be dangerous. Here we examine a previously undescribed behaviour in ants – the formation of well-defined faecal patches. Lasius niger ants were housed in plaster nests and provided with coloured sucrose solution. After two months, 1–4 well defined dark patches, the colour of the sucrose solution, formed within each of the plaster nests. These patches never contained other waste material such as uneaten food items, or nestmate corpses. Such waste was collected in waste piles outside the nest. The coloured patches were thus distinct from previously described ‘kitchen middens’ in ants, and are best described as ‘toilets’. Why faeces is not removed with other waste materials is unclear. The presence of the toilets inside the nest suggests that they may not be an important source of pathogens, and may have a beneficial role.